Behavioral Aspects and Their Impact on Purchasing Accounting System Implementation: A Quantitative Study: Aspek Perilaku dan Dampaknya pada Implementasi Sistem Akuntansi Pembelian: Studi Kuantitatif - Solvia Sriwulandari; Heri Widodo (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the influence of behavioral aspects, including attitudes, perceptions, and emotions, on the implementation of a purchasing accounting system in an organization. The research was conducted on employees of a specific company, with a sample size of 40 individuals, using accidental sampling as the quantitative research method. The findings reveal a significant positive impact of behavioral aspects on the implementation of the purchasing accounting system. This study underscores the importance of considering behavioral factors in effectively and efficiently implementing systems within organizations, providing valuable insights for companies seeking to optimize their operations and achieve their goals.Highlights : This study examines how attitudes, perceptions, and emotions impact the implementation of a purchasing accounting system in organizations. The research involved 40 employees of a specific company, utilizing accidental sampling as the research method. The results emphasize the significant positive influence of behavioral aspects on the successful implementation of purchasing accounting systems, highlighting the importance of considering these factors for organizational efficiency and goal achievement. Keywords: Behavioral Aspects, Purchasing Accounting System, Influence, Implementation, Organization